Optical Measurements Revealing Nonuniform Hole Mobility in Organic Electrochemical Transistors. (15th October 2015) - Friedlein, Jacob T.; Shaheen, Sean E.; Malliaras, George G.; McLeod, Robert R.
Abstract : Theoretical predictions and experimental results show that the carrier mobility in conjugated polymers depends on carrier concentration. However, existing models for organic electrochemical transistors (OECTs) assume uniform carrier mobility along the transistor channel despite variations in carrier concentration. Here, a model incorporating disorder‐induced nonuniform mobility is developed to describe the steady‐state behavior of OECTs. This model is tested using in situ optical measurements of an OECT channel to decouple the mobility and carrier concentration contributions to channel conductivity. It is found that unlike existing models, the nonuniform mobility model agrees with these measurements. Furthermore, it is found that the model matches current–voltage data over a wide range of device geometries and two different device architectures. Finally, it is shown that a 120% improvement of transconductance can be obtained by operating a sensor according to device parameters given by the nonuniform mobility model rather than those extracted from an existing model that assumes a uniform mobility. Ultimately, the model presented allows more accurate measurement of material properties via transistor characterization. This will enable better‐informed material optimization, development of more accurate transient models for OECTs, and more effective use of OECTs made from existing materials. Abstract : Simultaneous optical and electrical measurements reveal non‐uniform hole mobility in organic electrochemical transistors (OECTs). This non‐uniformity is explained via carrier hopping in an energetically disordered density of states. This explanation leads to a new electrostatic model for OECTs, provides simple current–voltage equations that agree with experiment better than existing models, and informs improved operation of OECTs for biosensing.